1987
DOI: 10.1523/jneurosci.07-03-00716.1987
|View full text |Cite
|
Sign up to set email alerts
|

Cue-sampling and goal-approach correlates of hippocampal unit activity in rats performing an odor-discrimination task

Abstract: Several techniques previously used to describe behavioral correlates of hippocampal unit and slow-wave activity are combined in a single odor-discrimination paradigm. Rats repetitively performed a sequence of behaviors during each trial: approach to a stimulus-sampling port, investigatory sniffing of the odor cue, orientation and approach toward a separate reward location, and water reward consumption. In a series of post hoc analyses, spike activity was timelocked to variations of each task event to uncover b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
193
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(221 citation statements)
references
References 30 publications
27
193
1
Order By: Relevance
“…By this point, it is pretty much accepted that under certain conditions, hippocampal pyramidal cells show correlations to non-spatial aspects [48,69,71,101,109,157,238,239,246,247,250] (see [33,173] for reviews, but see [147] for an alternative viewpoint). These non-spatial aspects include when animals change task within an environment [101], in response to components of a task in which goals change [48,69,157,247], even after salient events [202].…”
Section: Non-spatial Place Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…By this point, it is pretty much accepted that under certain conditions, hippocampal pyramidal cells show correlations to non-spatial aspects [48,69,71,101,109,157,238,239,246,247,250] (see [33,173] for reviews, but see [147] for an alternative viewpoint). These non-spatial aspects include when animals change task within an environment [101], in response to components of a task in which goals change [48,69,157,247], even after salient events [202].…”
Section: Non-spatial Place Cellsmentioning
confidence: 99%
“…These non-spatial aspects include when animals change task within an environment [101], in response to components of a task in which goals change [48,69,157,247], even after salient events [202]. In addition, hippocampal cells show place field changes with changes in environments or the available constellation of cues [17,90,93,129,148,181,219,223,250].…”
Section: Non-spatial Place Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ablation of the orbitofrontal region of both rats (9) and primates (34) is associated with deficits in olfactory discrimination. Hippocampal damage also compromises olfactory discrimination in rats, but only if the task includes the simultaneous presentation of two stimuli (5)(6)(7)26). Human studies have indicated that patients with focal brain lesions involving orbitofrontal (21,28,37) or anterior temporal cortex (8,10,21,30,37) are impaired on odor identification and discrimination tasks.…”
Section: Alcoholmentioning
confidence: 99%